THE EFFECT OF SELF-EFFICACY AND CAREER GOAL ORIENTATION ON STUDENTS' DIGITAL COMPETENCY DEVELOPMENT INTENTIONS: A CROSS-DISCIPLINARY STUDY - Abdul Jamil; Luqman Hakim; Muhammad Yusuf; Irpan Hidayat Hasibuan; Joko Sarono (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
Rapid digital transformation requires students to have adaptive digital competencies to be able to compete in a digitalized world of work. This study aims to analyze the influence of self-efficacy and career goal orientation on the intention of developing digital competencies in students across disciplines. This study uses an explanatory quantitative approach with a survey method of 200 active undergraduate and diploma four students from various fields of science. Data were collected through a questionnaire with a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results of the study show that self-efficacy and career goal orientation have a positive and significant effect on the intention of developing digital competencies, both partially and simultaneously, with a model that has a strong explainability. In addition, there is a difference in intentions between disciplines, where students in the field of science and technology show a higher level of intention than the social-humanities field. These findings confirm that psychological and motivational factors have an important role in shaping digital competency development intentions, not solely influenced by external factors. This research contributes to strengthening the integration of Self-Efficacy Theory, Goal Orientation Theory, and Theory of Planned Behavior, as well as providing practical implications for the development of higher education policies based on strengthening self-efficacy and digital career orientation.